ANALISIS FENOTIPE DAN PLOIDI TANAMAN MELON (Cucumis melo L.) HASIL PERLAKUAN EKSTRAK ETANOLIK DAUN TAPAK DARA (Catharanthus roseus [L] G. Don.) - Nugroho Nofriarno; Budi Setiadi Daryono; Avia Purnama Saputri; Estiyani Indraningsih (Biota, 2018)
Anti-mitotic agents such as colchicine have been used to induce polyploidy in various plants. On the other hand, vincristine and vinblastine are also antimitotic agent extracted from Periwincle (Catharanthus roseus [L] G. Don) were previously studied to produce autotetraploid on shallot tuber (Allium cepa L.). Therefore, in this study phenotype character and ploidy of muskmelon (Cucumis melo L.) produced by etanolic extract of periwikle leaves were determined. The effects of different concentration of etanolic extract of periwinkle leaves on polyploidy induction in muskmelon were examined. Melon seedling of two days old were immersed in 0.5%, 0.1%, and 0.05% for 8 hours. Then seedling was grown on the polybag and a drop of each concentration of periwinkle leaves’s etanolic extract was added into apical shoot. Melon seedling of ten days old were moved and cultivated and harvested on 60 days after cultivation. Phenotypic character such as: plant high, stem diameter, leaf area, fruit weight, fruit area around, flesh fruit thickness, skin fruit thickness, fruit horizontal diameter, fruit, vertical diameter, number of seeds, weight of 100 gram of seed, seed leght, seed width, and seed thickness were examined. The ploidy degree was determined by count of chromosome number root tips of second generation muskmelon sprout. Result of this study revealed that 0.05% etanolic extract of periwinkle leaves for 8 hours immersed is optimum concentration to induce autotetraploid muskmelon (4n=48). Autotetraploid phenotypic character of muskmelon produced by 0.05% etanolic extract of periwinkle leaves were generally bigger than control plants statistically significant in stem diameter, leaf area, and fruit horizontal diameter. The result also showed that the chromosome number of second generation autotetraploid muskmelon sprout was tetraploid (4n=48).